The Analysis of The Factors Causing Learning Difficulties in IPAS Subject of Merdeka Curriculum in Grade IV Elemantary School - Sa'adah, Nailatis; Hermita, Neni; Fendrik, Muhammad (Education Generation Journal, 2024)
The background of this research is that the learning objectives have not been achieved, which is indicated by the fact that there are still many students in class IVA who always get low scores in IPAS subjects because of factors that cause learning difficulties. The purpose of this study was to describe the factors that cause students' learning difficulties in the IPAS subject experienced by fourth grade students in elementary school. This type of research is qualitative research. The source of the data in this study were class IVA students at SDN 192 Pekanbaru. The amount of data from this study was 6 students, which the researcher took based on the students' lowest test scores. The time for collecting this data is in the even semester of the 2022/2023 school year. The data collection techniques used in this study were observation, interviews and documentation. Data processing was carried out by researchers in the form of descriptive text regarding the factors causing students' difficulties in IPAS subjects. The results of this study are described based on the results of observations and interviews that have been analyzed by the author. The results of the data obtained are that 2 indicators of factors that cause learning difficulties are included in things that cause students difficulty in learning. Based on the data that has been obtained, it can be seen that the factors causing student learning difficulties are disturbed student body health, poor student attitudes in learning, low student learning motivation, lack of teacher variation in teaching, inadequate use of learning media, infrastructure inadequate schools, unsupportive family environment and less than optimal understanding of the school curriculum.